2019
DOI: 10.2478/jomb-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Saliva diagnostic utility in patients with type 2 diabetes: Future standard method

Abstract: Summary Background The purpose of the present study was to assess saliva reliability in diagnosis and monitoring type 2 diabetes instead of blood. Methods Blood and unstimulated whole saliva were collected from 300 type 2 diabetic subjects and 300 healthy controls in fasting. Then, the salivary flow rate was calculated. All parameters including glucose, urea, amylase, total protein, albumin, C-reactive protein (CRP), immunoglobulin A (IgA), potassium, calcium and chloride were assessed in the supernatant, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…To date, evidence regarding salivary IgA in diabetes patients is limited and inconclusive. Some studies report significantly higher levels of salivary IgA in diabetes patients compared to those without 20 , while others demonstrated lower salivary IgA secretion rates 21 and concentrations in patients with diabetes 22 . The latter observation is in line with our finding that specifically focuses on type 1 diabetes patients progressing towards neuropathy and presenting a healthy periodontium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, evidence regarding salivary IgA in diabetes patients is limited and inconclusive. Some studies report significantly higher levels of salivary IgA in diabetes patients compared to those without 20 , while others demonstrated lower salivary IgA secretion rates 21 and concentrations in patients with diabetes 22 . The latter observation is in line with our finding that specifically focuses on type 1 diabetes patients progressing towards neuropathy and presenting a healthy periodontium.…”
Section: Discussionmentioning
confidence: 99%
“…leptin, insulin, nerve growth factor, IL’s, TNF-α, hepatocyte growth factor, common salivary protein 1, cortisol, lactic acid) have been explored in relationship with diabetes 27 , 30 32 , but often provided somewhat conflicting findings due to their various study designs and inclusion of both type 1 and 2 adult diabetic patients. For example, α-amylase enzyme levels were described as either higher 22 , 33 , similar 34 , or decreased 35 in diabetic patients in comparison to healthy individuals. Our adult type 1 diabetic study cohort demonstrated an increased trend in α-amylase, which extends results found in type 1 diabetic children 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the control of diabetes is done with blood tests, which is an invasive method. In saliva, glucose and urea levels are found to be in direct relation with blood levels (44). In diabetic patients, there was also an increase found in the levels of amylase, total protein, and electrolytes such as potassium, calcium and chloride (44,45).…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…Blood analysis in the form of Random, Fasting, or Post Prandial blood glucose levels is considered as the only conventional method to diagnose or monitor the disease. [ 2 ] hemoglobin A1c (HbA 1c ), the glycosylated Haemoglobin provides an accurate estimate of glucose levels in the blood over the past 23 months and helps overcome the inconsistency in records of at-home monitoring. [ 3 ] However, monitoring of blood glucose levels at frequent intervals can cause discomfort and mental trauma to many individuals.…”
Section: Introductionmentioning
confidence: 99%